Indigenous animal genetic resources in Sri Lanka. Status, potential and opportunities - Silva, P. (Cambridge University Press, 2011)
Sri Lanka is a tropical island in the Indian Ocean. Due to its geographical location and position, most parts of the country are hot and humid. Based on the annual rainfall, elevation, soil and on terrain condition, 46 agro-ecological zones could be identified within the island. The farming systems widely vary according to the agro-ecological conditions prevailing in different areas of the country. In order to meet various human needs such as food and draught power, farm animals have been used throughout the country. In Sri Lanka few species of animals are raised as farm animals including four major mammalian species, namely neat cattle, buffaloes, pigs and goats. Chicken is the most common avian species reared. Other than these species several other livestock and avian species such as sheep, rabbit, duck and quails are also raised under different environment and management systems. Agriculture is an important sector in the country where 30% of the land area is used for agriculture, most of which are smallholdings. In this context however, livestock plays a secondary role where crop cultivation is the dominant sector. The contribution of the livestock sector to the national GDP is 1.2% whereas that of total agriculture sector is 5.6%. According to the value of representation in GDP livestock plays a minor role though, it provides a source of occupation for a considerable population in the rural sub-sector of the country. The farm animals in Sri Lanka can be categorized into three major groups namely locally adapted and recently introduces and continually imported breeds. Out of the three categories, locally adapted breeds are the most threatened as their populations are gradually decreasing. Among the factors contributing to this diminishing trend, lack of information on the proper evaluation of local breeds is the main factor. Wild relatives of three major farm animal species, namely buffalo, pig and chicken inhabit the wildlife protected areas and the surroundings. Other than those wild species the wild relatives of quails and ducks could also be found in scrub jungles in all parts of the country. In the case of buffaloes and pigs, there is definite gene flow from the wild relatives to domesticated indigenous varieties in certain localities where there is a direct contact between wild relatives and domestic animals. In the case of jungle fowl, which is endemic to Sri Lanka there are no concrete evidence for such an interaction in breeding. Generally, most of the breeds of farm animals are widely distributed all over the country. However, population density is not even in all the provinces. Pigs are mostly found in the western coast of the country. Buffaloes are distributed in lowland areas and highly dense in central part of the country. The distribution of cattle is very distinct as the European pure breeds and their crossbreds are distributed in central hills and wet area of the country whereas exotic tropical crosses and indigenous varieties are found in dry lowland areas. Comparatively higher number of goats is found in dry lowlands, mostly in remote rural areas. Comparatively higher number of goats is found in dry lowlands, mostly in remote rural areas. The pattern of distribution of poultry is highly influenced by the number of commercial type birds. However, village chickens (the indigenous types) are found throughout the island under backyard system of rearing. Since livestock is an integral component in the agriculture sector of the country several livestock production systems could be identified. In most of these production systems, livestock is represented as a co-component or subcomponent within the system since the whole production system is crop based, mainly paddy. The role of the livestock in these farming systems vary according to the level of input of the livestock for the whole system and nature of service that it provides for the sustainability of the system. When the change of population size of different farm animal species is considered, the records of past few years demonstrate diminishing trends in almost all the major species except poultry. In the case of chicken and ducks the trends is towards slight increase. However, there are no separate statistics available for any of the indigenous species, hence the population trends of this category cannot be assessed or quantified. However, the general perception is that the indigenous categories are shrinking or phasing out gradually. The indigenous livestock categories posses many valuable characteristics such as high adaptability, high resistance to common disease, high fecundity, early maturity, good mothering ability, longivity etc. Ability to produce at low input level is the most unique feature demonstrated by all categories of indigenous livestock. However, the preference of the farmer demonstrated by all categories of indigenous livestock. However, the preference of the farmer towards indigenous livestock categories depends mainly on two factors, namely availability of resources and availability of marketing opportunities. There are many risks factors operating against the sustainability and the survival of the indigenous livestock categories. These factors include the pressure for high productivity/ high output levels, agricultural development/ settlement schemes, change of farming systems, fluctuation of market values, shrinkage of habitats, and change of systems of farming / farm operations and war and natural disasters. The present status and, trends in population size and utilization pattern of indigenous categories of farm animals reveal that the indigenous animals need a far better attention and consideration at national level development and planning programs than at present.